Culture–Sex Interaction and the Self-Report Empathy in Australians and Mainland Chinese - Zhao, Qing; Neumann, David L.; Cao, Yuan; Baron-Cohen, Simon; Yan, Chao; Chan, Raymond C. K.; Shum, David H. K. (Frontiers in Psychology, 2019)
Empathy is the ability to understand and share other people’s emotions. Researchers have debated whether Westerners and Asians differ in their self-report empathy. This study aimed to replicate a previously reported culture–sex interaction in self-report empathy using Australian and Mainland Chinese participants, to investigate the cultural differences in self-report empathy in each sex group, and to verify the mediating effects of three empathy-related traits (i.e., independent self-construal, interdependent self-construal, and personal distress) on the cultural difference in self-report empathy separately for female and male participants. In this study, scores on two self-report questionnaires of empathy, namely, the Empathy Quotient (EQ) and the Interpersonal Reactivity Index (IRI), were compared between 196 Australian Caucasian (101 males) and 211 Mainland Chinese (59 males) university students. Results first confirmed the significant culture–sex interaction and illustrated that the cultural differences in empathy scores were significant only for female (i.e., Australian females had higher scores than Mainland Chinese females) but not for male participants. Furthermore, results of mediation analyses indicated that higher self-report empathy in both females and males was related to higher interdependent self-construal (exhibited by Mainland Chinese) and less personal distress (exhibited by Australians), and particularly in females, also related to higher independent self-construal (exhibited by Australian females). The current study is one of few studies that suggest cultural differences in empathy are dependent on the sex of the participant. Moreover, the current findings have added new insights into the explanation of cultural differences in empathy using personal distress and self-construal for males and females separately.